Evaluation of silver nanoparticles as irrigating solution - Gomes Filho, João Eduardo [UNESP]; Silva, Fernando Oliveira [UNESP]; Watanabe, Simone [UNESP]; Tendoro, Karina Vanessa [UNESP]; Dalto, Luana Godoy [UNESP]; Pacanaro, Sara Vieira [UNESP]; Lodi, Carolina Simonetti [UNESP]; Melo, Fernanda Fragoso Ferreira de; Dezan Junior, Eloi [UNESP]; Cintra, Luciano Tavares Angelo [UNESP] (Dental Press International, 2013)
Introduction: Irrigation is an important procedure during root canal treatment once it can help cleaning those areas of the root canal system not directly reached by instruments Objective: The aim of this study was to evaluate the biocompatibility and disinfection ability of silver nanoparticles dispersion in comparison to 2.5% sodium hypochlorite. Methods: Thirty two rats individually received 4 infected and uninfected dentin tubes irrigated with 47 ppm and 23 ppm silver nanoparticles dispersion, 2.5% sodium hypochlorite, and saline solution. Sixteen rats received one infected and one uninfected dentin tube, as the control group. After 7 and 30 days, all the animals were killed, the tubes and surrounding tissues were removed, and prepared to be analyzed in light microscope. Qualitative and quantitative assessments of the reactions were carried out. Results: All solutions in uninfected tubes caused mild reactions after 30 days. All solutions in infected tubes caused severe reactions after 7 days and mild reactions after 30 days. The outcomes were similar to those of the uninfected control group, but better than those of the infected control group. Conclusions: It was possible to conclude that silver nanoparticles dispersion was biocompatible and may act as disinfectant in contaminated tubes, especially at 23 ppm.
Keywords: Biocompatibility; Connective tissue biology; Endodontics